2013
DOI: 10.1111/jam.12410
|View full text |Cite
|
Sign up to set email alerts
|

A rapid colorimetric screening method for vanillic acid and vanillin-producing bacterial strains

Abstract: Aim: To isolate a bacterial strain capable of biotransforming ferulic acid, a major component of lignin, into vanillin and vanillic acid by a rapid colorimetric screening method. Methods and Results: For the production of vanillin, a natural aroma compound, we attempted to isolate a potential strain using a simple screening method based on pH change resulting from the degradation of ferulic acid. The strain Pseudomonas sp. AZ 10 UPM exhibited a significant result because of colour changes observed on the assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Natural vanillin is desirable in the worldwide market despite its higher prices. Nevertheless, natural vanillin production by direct extraction from vanilla is subject to many problems, such as low concentration, making the extraction process expensive (Serra et al 2005;Zamzuri et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Natural vanillin is desirable in the worldwide market despite its higher prices. Nevertheless, natural vanillin production by direct extraction from vanilla is subject to many problems, such as low concentration, making the extraction process expensive (Serra et al 2005;Zamzuri et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some AC precursors, such as lignin, FA, guaiacol, catechol, among others, are released and converted into AC such as VA, vanillic alcohol, HBA, PHB and vanillin, (Harazono et al , Ito et al ; Zamzuri et al ). Specifically, the FA has also been proposed as a precursor in the biosynthesis of vanillin and vanillin glucoside, both considered the most abundant AC in mature vanilla beans (Hernández‐Hernández ; Salazar‐Rojas et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This genus has the capacity to produce high concentrations of vanillin (300 μg ml −1 ). However, the Enterobacter genus isolated from the roots of V. planifolia can also degrade and bioconvert FA to vanillin (18 µg ml −1 ) (Li et al ; Zamzuri et al ). Other studies confirmed that Citrobacter was the most efficient strain at metabolizing FA relative to other Gram‐negative bacteria (Ammar et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The colour became brownish, and a weak sweet smell was detected, probably due to vanillic acid production. Transformation of lignin-based aromatic acids or its compounds by microorganisms in vanillic acid has been investigated by several authors (Chen et al 1983;Ander et al 1984;Zamzuri et al 2013), showing that fragmentation of lignin can generate a flavouring compound. With advancing degradation, these characteristics were more easily detected.…”
Section: Sec Analysesmentioning
confidence: 99%